Legal certainty in sentencing of local legislative candidates involving village heads in election campaigns (Case study of Bireuen District Court decisions No. 29/Pid.Sus/2024/PN.Bir and No. 30/Pid.Sus/2024/PN.Bir) - Anzilahata Anzilahata; Riza Afrian Mustaqim; Nurul Fitria (Privietlab, 2026)
This study examines an election violation case in Bireuen District, where a DPRK candidate involved a village head (keuchik) in campaign activities, raising legal issues regarding the application of Articles 490 and 493 of the Election Law. The research focuses on analyzing judicial considerations and reviewing legal certainty in the decisions of PN Bireuen No. 29/Pid.Sus/2024/PN. Bir and 30/Pid.Sus/2024/PN. Beer. Using a qualitative normative juridical method with case, statute, and conceptual approaches, the primary data consist of court rulings and the Election Law, supported by legal literature. Findings reveal that the judges established both formal and material elements of the offense but imposed relatively light sentences, which undermined consistency and predictability of rulings. Although the legal norms were upheld, the decisions did not fully realize the principle of legal certainty, highlighting the need for harmonization in sentencing patterns to strengthen certainty in electoral law enforcement.